Assessment Of Vaccine Coverage By 30 Cluster Sampling Technique In Rural Gandhinagar, Gujarat - Jay K Sheth; Kartik N Trivedi; Jayshree B Mehta; Umesh N Oza (Medsci Publications, 2012)
Objectives: To assess the immunization status of children of Gandhinagar (Rural) district and to compare it with the NFHS3/DLHS3 coverage results. Materials & Methods: A Multi-Indicator Cluster Survey (MICS) was planned and community-based cross-sectional survey was conducted in April 2008. The Study was conducted using 30 cluster technique. Proforma designed by UNICEF, modified by experts and approved for uniform use by department of health & family welfare, Government of Gujarat was used as a study tool. Statistical analysis used: Simple proportions and Chi-square test. Results: Coverage for BCG, OPV3, DPT3 & Measles were 92.04%, 85.23%, 83.71% & 82.20% respectively. BCG scar was seen in 83.95% of children out of those who received BCG. The proportions of fully immunized children were 79.55%. Unimmunized children were 4.16%. Dropout rate was 9.05% for BCG-DPT3, 10.69% for BCG-Measles & 7.53% for DPT1-DPT3. Compared to NFHS3 (2005-06) as well as DLHS3 (Gandhinagar district, 2007-08) the current survey shows higher coverage for all vaccines except measles which was higher in DLHS3 (87.3%). Gender wise difference in the coverage of different vaccines or various dropout rates was not statistically significant. Conclusions: Although the vaccination coverage shows higher coverage than previous studies, it is still below the minimum targets set as national goal.